Do trade certifications alleviate economic and social deprivations of plantation workers? A study of the tea plantation sector in India. (1st January 2021) - Viswanathan, P.K.
Abstract : This paper explores the important question whether trade certifications alleviate the economic and social deprivations of workers in tea plantations in India. Following a critical assessment of the historic deprivations faced by tea plantation workers, the author reviews the potential implications of various certifications adopted by tea plantations in India, including, Fairtrade (FT), RFA, ETP and Trustea. As a case for empirical analysis, the paper specifically examines FT certification and its impacts on tea plantation workers with particular reference to three certified tea estates located in the Nilgiris region in Tamilnadu (South India) and Assam (North-East India). The analysis endorses many of the findings of earlier studies on Fairtrade certification. Yet, it also provides very useful additional insights in terms of explaining why the adoption of certifications, especially FT certification, by tea plantations does not yield the intended outcomes with respect to amelioration of the deprivations suffered by the plantation workers. It reveals that, despite more than two decades of engagement with FT certifications, tea plantations are unable to make significant improvements in the lot of the plantation workers due mainly to the fact that the FT premiums that the tea estates receive are nominal and quite variable across years. It concludes that, given that the domestic consumption demand for tea has been growing in India, it is also crucial to focus on the domestic market through the design and promotion of appropriate certification standards (integrating the finest elements of existing ones) that would contribute towards improving the status as well as working and living conditions of plantation workers. This would also help mitigate the huge disparity in wages and earnings of workers between the south and north Indian states that emerge from the study.